Respuesta :

Answer:

the second option

Step-by-step explanation:

in ax²+bx+c = 0:

[tex]x = \frac{-b+-\sqrt{b^2-4ac} }{2a}[/tex]

subtract both sides by 6 to get to this form, as the right side will be left with 0

6x² + 8x - 6 = 0

here, the coefficient for x² (a) is 6, the coefficient for x (b) is 8, and the remaining number added on (c) is -6

plugging our numbers into the formula, we get

[tex]x = \frac{-8+-\sqrt{(-8)^2-4(6)(-6)} }{2(6)}\\= \frac{-8+-\sqrt{64-(-144)} }{12} \\= \frac{-8+-\sqrt{208} }{12} \\ = \frac{-8+\sqrt{208} }{12} or \frac{-8-\sqrt{208} }{12}\\= 0.53518375848 or -1.86851709182\\= approximately -1.87, 0.54[/tex]